The Impact of Economic Size of Government on IncomeDistribution: Evidence from OECD Countries - Ceyhan, Turgay; Kostekçı, Ahmet; Göv, Abdullah (My University, 2021)
In this study, the relationship between taxes and public expenditures, that show the government?s economic sizeand income distribution, is analyzed. In the study covering the period 2000-2017 for 24 OECD countries, theTwo-Step System Generalized Method of Moments and the bootstrap version of Dumitrescu-Hurlin (2012) panelcausality test were used. According to the results of the Two-Step System Generalized Method of Moments, theexpansion in the government?s economic size increases the inequality. Findings of the panel causality test showunidirectional causality from taxes and expenditures to Gini
Keywords: İktisat